Temperature Effect of Crystalinity in Cellulose Nanocrystal from Oil Palm Empty Fruit Bunch (OPEFB) using Sonication-Hydrothermal Methods - Zulnazri Zulnazri; Fika Anjana; Achmad Roesyadi (Chemistry Department, The University of Brawijaya, 2017)
Production of cellulose nanocrystals (CNCs) from cellulose of oil palm empty fruit bunches (OPEFB) have been done. The delignification of OPEFB was mixed with 17,5% NaOH and carried out in the three-neck flask with refluxed for 2 hour at 80oC. Further the suspension was bleached with NaOCl 2% for 1 hour at 70oC. Then, to produce CNCs, Cellulose was firstly sonicated for 30 minutes at 40oC. After that cellulose was hydrolized at hydrothermal reactor for 0,1,2,3,4,5, hours at 110 and 120oC respectively. After filtration and washing, CNCs was analyzed by X-Ray Diffraction and the result shows that the grade of the highest CNCs crystalinity at consentration of HCL 2 M at a temperature of 110oC with reaction time of 2 hours is equal to 75.87%. It can be concluded that sonication-hydrothermal can increase the grade of crystalinity of cellulose nanocrystal.